Predictive factors and nomogram for the risk of cytokine release syndrome with anti-CD3 × CD20 bispecific antibodies for Chinese patients - Peng Sun; Cui Chen; Bai-Tian Zhao; Bo-Yan Zhang; Hang Yang; Yu Wang; Fei Xu; Kang-Ming Huang; Yin-Ting Liu; Mei-Shuo Ouyang; Jia-Jia Huang; Pan-Pan Liu; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Targeting CD3 × CD20 bispecific antibodies (BsAbs) represents a new milestone in the salvage therapy of relapsed/relapsed large B cell lymphoma and follicular lymphoma. However, cytokine release syndrome (CRS) remains one of the major concerns in clinical practice of CD3 × CD20 BsAbs. This study aimed to identify the potential predictive factors and to construct a nomogram of grade ≥ 2 CRS in CD3 × CD20 BsAbs in Chinese patients. Methods A total of 87 consecutive patients with B-NHL who received CD3 × CD20 BsAbs at Sun Yat-sen University Cancer Center from January 2021 to December 2023 were included and analyzed. Clinical data were collected, and various methods including machine learning algorithms were introduced. Results The median age of the patients was 55 years, and the median number of previous treatment lines was 2. CRS occurred in 42 patients (48.3%), including 27 cases of grade 1, 9 cases of grade 2, 5 cases of grade 3, and 1 case of grade 5. Four variables were revealed and selected: bulky disease (> 5 cm), number of previous treatment lines (≥ 3), monocyte-to-lymphocyte ratio (MLR), and platelet count (PLT). Bootstrap resampling was introduced for both internal validation and model building. A predictive nomogram was ultimately established, with the ROC–AUC of 0.867 (95% CI 0.719–0.954). Conclusion This study suggests four potential predictive factors and provides a feasible and easy-to-use nomogram for grade ≥ 2 CRS in Chinese patients for the first time, which is important for guiding personalized management and early intervention of CRS.